Alopecia Universalis following Alemtuzumab Treatment in Multiple Sclerosis: A Barely Recognized Manifestation of Secondary Autoimmunity—Report of a Case and Review of the Literature - Zimmermann, Julian; Buhl, Timo; Müller, Marcus (Frontiers in Neurology, 2017)
Secondary autoimmunity is the most frequent adverse event occurring in almost every other alemtuzumab-treated multiple sclerosis patient. We report a case of a patient with relapsing-remitting multiple sclerosis who reported smooth, circular areas of complete hair loss on both thighs 6 months after the second treatment cycle with alemtuzumab. The patient was diagnosed as having alopecia areata (AA). Within 3 months, AA progressed to complete loss of all body hair (alopecia universalis). Current literature rarely connects alemtuzumab with the onset of alopecia of autoimmune origin. Here, we report a little-noticed autoimmune disease affecting the skin, very likely being associated with alemtuzumab. We emphasize the necessity of careful clinical surveillance of alemtuzumab-treated patients for yet undescribed autoimmune diseases.